2014
DOI: 10.1186/1756-9966-33-11
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of NAD(P)H-quinone oxidoreductase 1 enhanced the susceptibility of cholangiocarcinoma cells to chemotherapeutic agents

Abstract: BackgroundCholangiocarcinoma (CCA) is highly resistant to most of the known chemotherapeutic treatments. NAD(P)H-quinone oxidoreductase 1 (NQO1) is an antioxidant/detoxifying enzyme recently recognized as an important contributor to chemoresistance in some human cancers. However, the contribution of NQO1 to chemotherapy resistance in CCA is unknown.MethodsTwo CCA cell lines, KKU-100 and KKU-M214, with high and low NQO1 expression levels, respectively, were used to evaluate the sensitivity to chemotherapeutic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 25 publications
(44 reference statements)
0
52
0
Order By: Relevance
“…NAD(P)H:quinone oxidoreductase 1 (NQO1; EC 1.6.5.2), one of the detoxifying enzymes with antioxidant properties, has been proposed to be associated with the chemotherapeutic response of CCA (5,8). NQO1 is generally recognized as a 'cell protector', its induction in response to various noxious stimuli provides protection for cells against oxidative damage and oxidative stress-associated pathological conditions including cancer (9,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NAD(P)H:quinone oxidoreductase 1 (NQO1; EC 1.6.5.2), one of the detoxifying enzymes with antioxidant properties, has been proposed to be associated with the chemotherapeutic response of CCA (5,8). NQO1 is generally recognized as a 'cell protector', its induction in response to various noxious stimuli provides protection for cells against oxidative damage and oxidative stress-associated pathological conditions including cancer (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of NQO1 during carcinogenesis may provide cancer cells with a growth advantage and protection against extreme oxidative stress environments (10,11). Considering the function of NQO1, an increased NQO1 expression level may be associated with disappointing outcomes to certain cancer treatment modalities, including chemotherapy and radiotherapy, which induces cancer cell death by the generation of free radicals and oxidative damage (5,8).…”
Section: Introductionmentioning
confidence: 99%
“…Cholangiocarcinoma is highly resistant to chemotherapy and NQO1 protein, NAD(P)H-quinone oxidoreductase 1, has been shown to play a cooperative role in cancer chemoresistance [64]. Recent data by Zeekpudsa et al [65] showed that NQO1 knock-down increased the response of CCA cells to the chemotherapeutic drugs 5-fluorouracil and gemcitabine. Altogether, these findings suggest a potential role for NQO1 in treatment of patients with CCA.…”
Section: Figurementioning
confidence: 99%
“…A high expression of this antioxidant/detoxifying enzyme has been found in the aggressive C2 subtype of HB and is associated to significantly reduced survival compared to patients with lower expression of this gene [24]. NQO1 catalyzes the reduction of anthracyclines to less potent semiquinone radicals and it has been demonstrated that enhanced expression of NQO1 confers resistance to doxorubicin and other chemotherapeutic agents in cholangiocarcinoma cell lines [25]. Inactivating mutations have also been found in the thioredoxindomain containing genes TXNDC15 and TXNDC16, also involved in the regulation of mechanism involved in oxidative stress status [23].…”
Section: Mocmentioning
confidence: 99%